2022
DOI: 10.1093/stcltm/szac021
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Injection of Mesenchymal Stromal Cell Cultured on 3D Fiber Ameliorates Multiple Organ Damage in Murine Lupus

Abstract: Up to 60% of patients with systemic lupus erythematosus (SLE) experience autonomic symptom. Sympathetic nervous system damage can cause dysfunction of the bone marrow that activates inflammatory cells, potentially causing multiple organ damage. We hypothesized that sympathetic nervous system damage would induce bone marrow dysfunction with multiple organ damage in SLE, and that multiple organ damage could be improved by therapy targeting the nervous system. Here, we showed that damage to autonomic nerves and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…2I). Previous studies demonstrated that the expression of TH in LC was signi cantly lower in MRL/lpr mice [30]. To determine whether the taVNS relieved this impairment, we observed the expression of TH in the two groups of mice, found the number of TH + cells were signi cantly higher in the mice that received taVNS (Fig.…”
Section: Tavns Alleviated the Neuropsychiatric Sle (Npsle)-like Sympt...mentioning
confidence: 83%
See 1 more Smart Citation
“…2I). Previous studies demonstrated that the expression of TH in LC was signi cantly lower in MRL/lpr mice [30]. To determine whether the taVNS relieved this impairment, we observed the expression of TH in the two groups of mice, found the number of TH + cells were signi cantly higher in the mice that received taVNS (Fig.…”
Section: Tavns Alleviated the Neuropsychiatric Sle (Npsle)-like Sympt...mentioning
confidence: 83%
“…Noradrenaline has an important role in many psychiatric and neurodegenerative disorders and most of the noradrenaline released in the brain is supplied by LC [55,56]. Besides, LC neurons loss is an early feature of depression and neurodegenerative diseases [57,58], which may also exist in MRL/lpr mice [30]. In current study, we found taVNS protected TH + neurons in LC, indicating that the therapeutic effects of taVNS may be related to its activation of LC noradrenergic cells.…”
Section: Discussionmentioning
confidence: 99%